DEVELOPMENT AND EVALUATION OF IN SITU GELS OF MOXIFLOXACIN FOR THE TREATMENT OF PERIODONTITIS - Hareesh Babu Kunche; Mohammed Gulzar Ahmed; Narayana Charyulu Rompicharla (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2012)
Gel dosage forms are successfully used as drug delivery systems to control drug release and protect the medicaments from a hostile environment. The main objective of the present investigation is to formulate and evaluate in situ gels of moxifloxacin for the treatment of periodontitis using gellan gum and sodium alginate based on the concept of ion activated systems. The system utilizes polymers that exhibit sol-to-gel phase transition due to change in specific physico-chemical parameters. Sol-to-gel transformation occurred in the presence of monovalent/divalent cations. It was found that increase in the concentration of calcium ions produced stronger gels. Formulations were evaluated for gelling capacity, drug content, clarity, viscosity, gel strength, spread ability, microbiological studies and in vitro release. The results shown by the above characterization studies were found to be satisfactory. Experimental part showed that viscosity of sols and gel strength was increased with increase in the concentration of polymers and the sustained release of drug was observed. The formulations were therapeutically efficacious, sterile and provided sustained release of the drug over a period of time. These results demonstrated that the developed system is an alternative to conventional drug delivery systems, provides patient compliance and economical.Key words: in situ gels, moxifloxacin, periodontitis, polymers, Ion activation.